Barriers and facilitators to hepatitis B vaccination among sex workers in Vancouver, Canada: Implications for integrated HIV, STI, and viral hepatitis services. (October 2019) - Ranjan, Anuisa; Shannon, Kate; Chettiar, Jill; Braschel, Melissa; Ti, Lianping; Goldenberg, Shira
Highlights: Sex workers face sub-optimal access to hepatitis B virus (HBV) prevention. Im/migrant women sex workers had lower odds of HBV immunization. Participants accessing HIV testing and who used drugs had higher odds of immunization. Community-based, culturally safe services are needed to address gaps in HBV prevention. Abstract: Objectives: Sex workers (SWs) face an increased burden of sexually transmitted and blood-borne infections, yet little is known regarding hepatitis B virus (HBV) prevention and care. This study was performed to characterize cross-sectional and prospective correlates of HBV vaccination among SWs in Vancouver. Methods: Questionnaire data were drawn from a community-based cohort of SWs (2010–2017). Multivariable logistic regression was used to examine correlates of lifetime self-reported HBV vaccination. Multivariable generalized estimating equation (GEE) regression was used to assess correlates of recent vaccination. Results: Among 855 participants, 68.3% reported lifetime HBV vaccination. Multivariable logistic regression showed that im/migrants (adjusted odds ratio (AOR) 0.50, 95% confidence interval (CI) 0.32–0.78) had lower odds of vaccination and that those using injection drugs (AOR 1.88, 95% CI 1.27– 2.78) and those who had undergone HIV testing (AOR 1.94, 95% CI 1.14–3.29) had higher odds of vaccination. In the multivariable GEE analysis, HIV seropositivity (AOR 1.93, 95% CI 1.26–2.97) and recent STI testing (AOR 2.95, 95% CI 1.99–4.39) correlated with recent HBV vaccination. Conclusions: Im/migrant SWs from HBV-endemic settings appear to face gaps in HBV prevention. Evidence-based interventions addressing gaps in voluntary HBV prevention and care are needed, including community-based and culturally safe services. Injection drug use and HIV testing were linked to enhanced vaccination, suggesting that harm reduction and HIV programmes may facilitate linkage to HBV prevention.